TEACHING VOCABULARY FOR CHILDREN EFFECTIVELY - Normuhammedova Husnidakhon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: For children, vocabulary can open up a world of communication (listening, speaking, reading, and writing), and developing a large vocabulary can be enjoyable and useful for teaching them about the outside world. The correct vocabulary techniques can be beneficial. There are a few things we want you to bear in mind as we go over some fun, practical advice on how to teach language to your child. These will support both your child and you in maintaining concentration while having fun.